Heat transfer performance and optimization of a close-loop R410A flash evaporation spray cooling - Lin, Yan-Ke; Zhou, Zhi-Fu; Fang, Yu; Tang, Hong-Lin; Chen, Bin (Applied thermal engineering, 2019)
•Heat transfer performance of close-loop R410A spray cooling was first studied.•CHF and HTC first presented an increase and then a decrease with spray distance.•Appropriate nozzle diameter of 0.56 mm dictated a superior cooling performance.•CHF of 264 W/cm2 was achieved while surface temperature was below 30 °C at 25 mm. Flash spray cooling has been subject to increased attention because of its high heat dissipation capacity at low surface temperature in the application of high power technologies. In this study, experiment was conducted to study the effects of spray distance and nozzle diameter on heat transfer performance in a closed-loop R410A flash spray cooling system for the first time. Five spray distance from 10 mm to 30 mm and three nozzles with same internal structure but different diameters of 0.51, 0.56 and 0.69 mm were employed. The experiment results indicated the critical heat flux (CHF) value firstly increased and then deceased with the increase of spray distance, which is consistent with previous research of spray cooling with FC-72 and FC-87. The highest CHF value reached 264 W/cm2 while maintaining surface temperature below 30 °C and heat transfer coefficient (HTC) was about 210 kW/(m2·K) at 25 mm, which were 60% higher than those at 10 mm spray distance. The nozzle with medium orifice diameter of 0.56 mm showed a superior cooling performance, instead of larger nozzle with higher refrigerant flow rate. Therefore, there existed a counterbalance between the mass flow and outlet velocity in determining the optimum nozzle orifice diameter.